Virtual reconstruction of the Upper Palaeolithic skull from Zlatý Kůň, Czech Republic: Sex assessment and morphological affinity - Rmoutilová, Rebeka; Guyomarc'h, Pierre; Velemínský, Petr; Šefčáková, Alena; Samsel, Mathilde; Santos, Frédéric; Maureille, Bruno; Brůžek, Jaroslav (PLoS One, 2018)
The incomplete cranium discovered at the Zlatý kůň site in the Bohemian Karst is a rare piece of skeletal evidence of human presence in Central Europe during the Late Glacial period. The relative position of cranial fragments was restored and missing parts of the cranium were virtually reconstructed using mirroring and the Thin-plate splines algorithm. The reconstruction allowed us to collect principal cranial measurements, revise a previous unfounded sex assignment and explore the specimen's morphological affinity. Visual assessment could not reliably provide a sexual diagnosis, as such methods have been developed on modern populations. Using a population-specific approach developed on cranial measurements collected from the literature on reliably sexed European Upper Palaeolithic specimens, linear discriminant analysis confirmed previous assignment to the female sex. However, caution is necessary with regard to the fact that it was assessed from the skull. The Zlatý kůň specimen clearly falls within the range of Upper Palaeolithic craniometric variation. Despite the shift in cranial variation that accompanied the Last Glacial Maximum (LGM), the Zlatý kůň skull exhibits a morphological affinity with the pre-LGM population. Several interpretations are proposed with regard to the complex population processes that occurred after the LGM in Europe.
Keywords: Skull; ženské pohlaví; pohlavní dimorfismus; zkameněliny; Česká republika; Humans; Sex Characteristics; Cephalometry; lidé; kefalometrie; Discriminant Analysis; Fossils; lebka; Female; Czech Republic; diskriminační analýza